PENERAPAN ASESMEN FORMATIF UNTUK MENINGKATKAN LITERASI SAINS PADA MATERI PENCEMARAN LINGKUNGAN - Bella Aprilia, Gita; Wahyu Budi Sabtiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research examines the application of formative assessment to improve science literacy in environmental pollution material at SMPN 11 Surabaya. Science literacy is a crucial competency in the 21st century, yet Indonesian students' performance in PISA 2022 showed only 34% reached basic competency level. This pre-experimental study employed a one-group pretest-posttest design involving 31 seventh-grade students. Formative assessment was integrated into Problem Based Learning through various techniques including student worksheets with feedback columns, peer assessment, self-assessment, and guided reflection. Data were collected through observation sheets, pretest-posttest, and student response questionnaires. Results indicate: (1) learning implementation was excellent at 97.33%; (2) science literacy significantly improved with average N-gain of 0.5 (moderate category), confirmed by Wilcoxon Signed Rank Test (Z = -4.092, Sig. = 0.000); and (3) student responses were very positive at 91.09%. The highest N-gain was achieved in identifying scientific problems (0.71, high category). These findings confirm that systematic formative assessment integration in PBL effectively enhances science literacy in environmental pollution topics. Keywords: formative assessment, science literacy, environmental pollution, Problem Based Learning